2013
DOI: 10.4055/cios.2013.5.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity after Total Hip Replacement in Korean Patients: How They Do, What They Want, and How to Improve

Abstract: BackgroundConcerns of patients on sexual activity after total hip arthroplasty have not been well studied in Asian patients. This study aimed to determine the following: (1) what are the concerns of patients related to sexual activity after total hip arthroplasty? (2) what are the changes in sexual activity after total hip replacement in Korean patients?MethodsDetails of sexual activity and concerns were obtained using a questionnaire designed specifically for the study. The questionnaire was administered to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 25 publications
(30 reference statements)
2
42
1
4
Order By: Relevance
“…Difficulties having sex is a major factor that affects the quality of life of patients before undergoing THA [13,15,16]. Many patients attribute these difficulties to the underlying hip arthritis and expect an improvement in their sexual activities or participating in such activities as a result of their THA [9,12,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties having sex is a major factor that affects the quality of life of patients before undergoing THA [13,15,16]. Many patients attribute these difficulties to the underlying hip arthritis and expect an improvement in their sexual activities or participating in such activities as a result of their THA [9,12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations in sexual activity are common among patients with hip arthritis [6] and patients often express that these issues can cause unhappiness or tension in their relationships [6,10,16]. Although patients frequently do not explicitly mention better sexual function as a desired result of surgery, many expect improvement after THA [9,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…As human beings can be sexually active at all ages [ 12 ], the total number of sexually active patients undergoing THR will increase. Given the fact that SF is seldom discussed, [ 12 ], Sexual Difficulty (SD) might be under-diagnosed in patients with HA; however, while there are some recent international studies into this topic [ 13 15 ], an overview of the literature is lacking. The aim of this study, therefore, was to provide a systematic review of the literature, with the aim of summarising the effects of THR on patients’ SQoL.…”
Section: Introductionmentioning
confidence: 99%
“…The patients' fear for dislocation has been emphasized (up to 80%) in previous literature [8]. In addition, the female patients in this study changed their preferred sexual positions after THA in non-recommended positions, mostly due to difficulties with the leg position [8]. Unknown is if this would lead to more dislocations of the prosthesis more easily.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 78%
“…Authors suggest SF should be routinely addressed with all patients undergoing THA [2]. Within fifty years of research, only a few studies have examined the impact of HA on SF and improvement of SF after THA [3][4][5][6][7][8][9]. Since 1991, Stern et al (1991) found that nearly 80% of patients (who were satisfied with the THA result) felt the need for more information about SF afterwards; and in 20% sexual dysfunction (SD) had been an argument to undergo THA [4].…”
Section: Introductionmentioning
confidence: 99%